Dietary Ferulic Acid Ameliorates Metabolism Syndrome-Associated Hyperuricemia in Rats via Regulating Uric Acid Synthesis, Glycolipid Metabolism, and Hepatic Injury - Zhang, Nanhai; Zhou, Jingxuan; Zhao, Lei; Wang, Ou; Zhang, Liebing; Zhou, Feng (Frontiers in Nutrition, 2022)
Ferulic acid is a well-known phenolic acid compound and possesses multiple health-promoting and pharmacological effects. Metabolic syndrome (MetS) and hyperuricemia (HUA) have become health problems worldwide and are closely connected. The aim of this study was to explore the influence of ferulic acid on MetS-related HUA and its underlying mechanisms. Rats were administered high-fructose and high-fat diet (HFFD) with or without ferulic acid (0.05% and 0.1%) for 20 weeks. Intake of HFFD resulted in obesity, hyperglycemia, insulin resistance, and dyslipidemia, which were alleviated by ferulic acid consumption. Treatment of rats with ferulic acid diminished the levels of lipids and inflammatory cytokines and enhanced the activities of antioxidant enzymes in the liver caused by HFFD. Additionally, administration of ferulic acid blocked a HFFD-induced elevation in activities and mRNA expression of enzymes involving in uric acid (UA) synthesis. Molecular docking analysis denoted that ferulic acid bound to the active center of these enzymes, indicative of the potential interaction with each other. These two aspects might partially be responsible for the decrement in serum UA content after ferulic acid ingestion. In conclusion, ferulic acid supplementation ameliorated lipid and glucose metabolic abnormalities, hepatic damage, and UA formation in MetS rats. There was a dose correlation between lipid deposition and UA synthesis-related indicators. These findings implied that ferulic acid could be applied as a promising dietary remedy for the management of MetS-associated HUA.